Collective leadership as institutional work: interpreting evidence from Mound Bayou. (November 2017) - Novicevic, Milorad M.; Humphreys, John H.; Popoola, Ifeoluwa T.; Poor, Stephen; Gigliotti, Robert; Randolph-Seng, Brandon
In this article, we refine and extend the conceptualization of collective leadership by examining how institutional work can play a central role in the emergence of collective leadership success or failure through conflict. Specifically, based on historical traces collected from the first African American town in Mississippi, Mound Bayou, which was founded and led by a group of ex-slaves, we conceptualize collective leadership as a compilational process and elucidate the development of collective leadership amid the relational and inspirational aspects of conflict that arose among this cadre of historical collective leaders. We selected the case of Mound Bayou because the specifics of the case allowed us to explore how collective leadership emerged, and over time, led to conflict engendered by issues that arose within the institutional processes of formation, maintenance, and transformation of the town. We used interpretivist epistemology into which we incorporated and utilized historiometric methodology to code and interpret salient archival data. Based on this analysis, we inductively theorize the process by which the leaders of Mound Bayou collectively forged and led, in both cooperative and conflicting manner, the first African American community in the Mississippi Delta.